Support characteristics of eco-spiral pile with respect to twisting angle and ratio of borehole diameter to pile width - Kang, S.; Noh, J.; Jang, Hyong Doo (Taylor & Francis, 2017)
This study numerically analysed the characteristics of eco-spiral piles (Eco-SPs) as multi-purpose geotechnical supports. The behaviour of eco-spiral piles in the ground was studied with respect to their twisting angle and the ratio of borehole diameter to eco-spiral pile width using FLAC-3D based on the finite-difference method. A cement mortar grout was modelled to sustain the eco-spiral pile in a sandy soil. Relationships were found among the eco-spiral pile’s twisting angle, pull-out load and maximum shear stress. The results should aid the further design of the bolts for application in a range of circumstances.